Environmental perception of desertification process in Peru - Quispe Cornejo, Silvia (2013)
“Environmental Perception Process of Desertification in Perú”, try to do an analysis and evaluation of Peruvian territory in terms of enviromental degradation due to problems of biodiversity loss, progressive loss of productive capacity land ecosystem in the climaterelevant ecological Peruvian territory. The purpose is to know the territorial spaces with problems of environmental degradation and prevention alternatives to existing problems. To achieve the goals you have to gather preliminary information and propose alternative development that can contribute to the welfare of the population emphasizing the danger in decreased food production in the future.